Impact of Nepotism on Turnover Intention and Service Recovery Performance; The Case of Private Hospitals in TRNC - Farahmand, Negar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: Nepotism is actually an ethical problem in any organization where it is condoled. It has been shown that nepotism has a serious and negative implication where it is entrenched, This tends to destroy organizational harmony and motivation among the employee. There is also a tendency for conflict when disharmony and dissatisfaction take hold in the organization.it found significant level of affective organizational commitment in our sample of study which tremendously reduced the negative impact of nepotism of job satisfaction in our sample. Hence, we established on the bases of our test result that nepotism do not really negatively affect organizational commitment in our sample. Furthermore, the estimated model and test result confirmed the significance of employee‟s job satisfaction and its positive impact of service recovery in our sample of study. We however found a weak positive relationship between turnover intention and organizational commitment in our sample. it estimated result and test statistic revealed a weak association between job satisfaction and turnover intention on the basis of which we did not accept the hypothesis that Job satisfaction is positively correlated with turnover intention. On the other hand, it found a significant positive relationship between job stress and nepotism in our sample of study. Keywords: nepotism, affective organizational commitment, job satisfaction, job stress, turnover intention. ………………………………………………………………………………………………………………………… ÖZ: Kayırmacılık işletmelerin en büyük ahlaki sorunu olmuştur. Kayırmacılığın olduğu yerlerde ciddi şekilde olumsuz etkileri tespit edilmiştir. Bu ise mevcut olan harmoniyi ve çalışanların motivasyonunu bozmaktadır. Bunun yanında işletmede uyumsuzluk ve memnuniyetsizliğe de neden olabilmektedir. Çalışmamızda kayırmacılığın örgütsel bağlılığı olumsuz etkilediği yönünde yeterli kanıt bulunamamıştır. Tahmini model ve test sonuçları da çalışan tatmininin müşterinin hizmeti tekrar satın almasını olumlu etkilediğini tespit etmiştir. Çalışmamızın bir bulgusu da işten ayrılma niyeti ve örgütsel bağlılık arasında zayıf bir ilişkinin olmasıdır. Diğer yandan iş tatmini ile işten ayrılma niyeti arasında da örneğimizde zayıf bir ilişki olduğu tespit edilmiştir. Anahtar kelimeler: kayırmacılık, örgütsel sadakat, iş tatmini, işten ayrılma niyeti.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2013. Supervisor: Assoc. Prof. Dr. Mustafa Tümer.
Keywords: Business Administration; Marketing Management; Organizational Behavior - Private Hospitals - Cyprus, North; nepotism, affective organizational commitment, job satisfaction, job stress, turnover intention